2015
DOI: 10.1182/blood-2014-04-568188
|View full text |Cite
|
Sign up to set email alerts
|

Jun-regulated genes promote interaction of diffuse large B-cell lymphoma with the microenvironment

Abstract: Key Points Elevated Jun signaling promotes lymphoma growth and dissemination to extranodal sites. Jun-regulated genes mediate the interaction of malignant cells with stromal cells and adhesion to extracellular matrix proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 48 publications
4
49
0
Order By: Relevance
“…In this regard, the function of SH3BP5 resembles that of ibrutinib, a BTK inhibitor that is highlighted for its remarkable antitumor effect in B‐cell malignancies 17, 18. SH3BP5 also interacts with c‐Jun NH2‐terminal kinase (JNK) 19, which is required for survival and proliferation of B‐cell lymphoma cells 20, 21. The endogenous level of SH3BP5 positively regulates JNK 22, 23; however, the overexpressed SH3BP5 inhibits JNK 24.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the function of SH3BP5 resembles that of ibrutinib, a BTK inhibitor that is highlighted for its remarkable antitumor effect in B‐cell malignancies 17, 18. SH3BP5 also interacts with c‐Jun NH2‐terminal kinase (JNK) 19, which is required for survival and proliferation of B‐cell lymphoma cells 20, 21. The endogenous level of SH3BP5 positively regulates JNK 22, 23; however, the overexpressed SH3BP5 inhibits JNK 24.…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum levels of bFGF have been reported in CLL, and plasma cell myeloma and expression of bFGF was found in tumor cells in CLL/SLL, FL, DLBCL, MCL, Burkitt and lymphoblastic lymphomas [55]. Interestingly, our recent study revealed that the direct interaction of DLBCL cells with mesenchymal cells strongly enhanced the production of bFGF and VEGF by lymphoma cells [56].…”
Section: Vessels and Endothelial Cellsmentioning
confidence: 93%
“…Consequently, the residual low levels of p-JNK observed after treatment with HG6-64-1 may lead to a better therapeutic window compared with direct JNK inhibitors. However, Jun-regulated genes activation was recently reported to promote lymphoma growth and dissemination to extranodal sites in DLBCL, 41 and the JNK pathway was reported as a therapeutic target in ABC-like DLBCL 42 ; so it is possible that direct JNK inhibition should be revisited in future studies.…”
Section: Discussionmentioning
confidence: 99%